2016
DOI: 10.1186/s12974-016-0752-y
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins abrogate glutamate-induced AMPK activation, oxidative stress, neuroinflammation, and neurodegeneration in postnatal rat brain

Abstract: BackgroundGlutamate-induced excitotoxicity, oxidative damage, and neuroinflammation are believed to play an important role in the development of a number of CNS disorders. We recently reported that a high dose of glutamate could induce AMPK-mediated neurodegeneration in the postnatal day 7 (PND7) rat brain. Yet, the mechanism of glutamate-induced oxidative stress and neuroinflammation in the postnatal brain is not well understood. Here, we report for the first time the mechanism of glutamate-induced oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 50 publications
1
82
0
3
Order By: Relevance
“…Of note, AMPK is a major downstream molecule of APN signaling. In general, AMPK acts as the cellular energy or fuel sensor responsible for the maintenance of cellular energy homeostasis in the body and is normally activated in response to an increase in the intracellular AMP/ATP ratio [73][74][75], e.g., the depletion of cellular energy by stress, starvation, hypoxia, or other means causes an increase in intracellular AMP and thereby, allosterically activates AMPK through phosphorylation of its α-subunit at Thr-172 by upstream kinases [76]. Reduced circulating APN levels have been observed in aged obese individuals and obese patients with type 2 diabetes mellitus [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, AMPK is a major downstream molecule of APN signaling. In general, AMPK acts as the cellular energy or fuel sensor responsible for the maintenance of cellular energy homeostasis in the body and is normally activated in response to an increase in the intracellular AMP/ATP ratio [73][74][75], e.g., the depletion of cellular energy by stress, starvation, hypoxia, or other means causes an increase in intracellular AMP and thereby, allosterically activates AMPK through phosphorylation of its α-subunit at Thr-172 by upstream kinases [76]. Reduced circulating APN levels have been observed in aged obese individuals and obese patients with type 2 diabetes mellitus [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Published data suggest that the neuroprotective effects of berry fruits are associated with their polyphenolic compounds, particularly, anthocyanins [ 37 , 38 ]. For instance, anthocyanins have been reported to protect against inflammatory and oxidative stress mediated neuroinflammation and neurodegeneration in adult mouse cortex [ 39 ], as well as in brains of postnatal rats [ 40 ], and rats fed a high-fat diet [ 41 ]. In light of these data, we designed the current study to evaluate the potential neuroprotective effects of polyphenolic-enriched extracts of six common edible berries, namely, blackberry, black raspberry, blueberry, cranberry, red raspberry, and strawberry.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting neuroinflammation and oxidative stress are the other pathological processes involved in brain aging and neurodegeneration (Lee et al, 2008;Mishra et al, 2016;Shah et al, 2016). It has been reported that neuroinflammation is a key player in various neurological disorders, including neurodegenerative illnesses and CNS injury (Chen et al, 2016;Yang and Zhou, 2018).…”
Section: The Possible Mechanism Of Actions Of Cef In Neurological Dismentioning
confidence: 99%